Excision of Mucocele Using Diode Laser in Lower Lip - Subramaniam Ramkumar; Lakshmi Ramkumar; Narasimhan Malathi; Ramalingam Suganya (Case Reports in Dentistry)
Mucoceles are nonneoplastic cystic lesions of major and minor salivary glands which result from the accumulation of mucus. These lesions are most commonly seen in children. Though usually these lesions can be treated by local surgical excision, in our case, to avoid intraoperative surgical complications like bleeding and edema and to enable better healing, excision was done using a diode laser in the wavelength of 940 nm.